ACUTE ORAL TOXICITY OF BAUHINIA VARIEGATA AND MADHUCA LONGIFOLIA IN MICE - KHARE, PRAGATI; KISHORE, KAMAL; SHARMA, DINESH KUMAR (International Journal of Current Pharmaceutical Research, 2022)
Objective: Bauhinia variegata and Madhuca longifolia, which belongs to Leguminosae and Sapotaceae, respectively, is traditionally used in India for the cure of many diseases. This study represents the result of acute oral toxicity of Bauhinia variegata and Madhuca longifolia on swiss albino mice. Methods: Following acute oral administration of 2500 mg/kg crude extracts of Bauhinia variegata and Madhuca longifolia to swiss albino mice, no mortalities or evidence of adverse effects were observed. Results: The results of this study agree with those of in vitro experiments, indicating that the use of Bauhinia variegata and Madhuca longifolia leaves is scientifically validated. Conclusion: The result was in agreement with that of in vitro experiments, whereby the crude extracts of Bauhinia variegata and Madhuca longifolia did not show toxicity. Based on the outcome of acute toxicity in experimental mice, the crude extracts of both Bauhinia variegata and Madhuca longifolia could be regarded as safe in experimental mice. Further toxicity study over a longer period of time involving detection of effects on vital organ functions would ensure that the plants are safe for human consumption.